2019
DOI: 10.1002/ddr.21490
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐neuroinflammatory effects of tannic acid against lipopolysaccharide‐induced BV2 microglial cells via inhibition of NF‐κB activation

Abstract: Microglia mediated neuroinflammation is known to cause various neurodegenerative and neurological ailments. Tannic acid is a natural polyphenol which has been reported to possess antioxidant, anti‐inflammatory, anticarcinogenic, antimutagenic, antitumor, and antimicrobial activities. As there are no reports till date on the anti‐neuroinflammatory effects of tannic acid, this study was conducted to analyze the possible mechanism and pathway involved in the prevention of neuroinflammation by tannic acid in BV2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
(24 reference statements)
2
25
1
1
Order By: Relevance
“…Although tannic acid treatment reduced nitrite production by 38% from αSYN-challenged microglia, this was not a statistically significant decrease, which could be due to the nitrite concentration approaching the detection limit of the Griess Reagent (2.5 µM) ( Figure 5A). While previous research has shown that tannic acid can reduce the production of neuroinflammatory factors such as ROS, NO and TNF-α from LPS-treated microglia via the suppression of the NF-κB pathway, our results show that tannic acid only reduces intracellular ROS production but does not have an appreciable effect on the other two markers (Figures 5A-D; Wu et al, 2019). This could potentially suggest that the rate at which tannic acid associates with αSYN is much faster than its interaction with other signaling molecules involved in the pathway (Shaham-Niv et al, 2018).…”
Section: Discussioncontrasting
confidence: 98%
“…Although tannic acid treatment reduced nitrite production by 38% from αSYN-challenged microglia, this was not a statistically significant decrease, which could be due to the nitrite concentration approaching the detection limit of the Griess Reagent (2.5 µM) ( Figure 5A). While previous research has shown that tannic acid can reduce the production of neuroinflammatory factors such as ROS, NO and TNF-α from LPS-treated microglia via the suppression of the NF-κB pathway, our results show that tannic acid only reduces intracellular ROS production but does not have an appreciable effect on the other two markers (Figures 5A-D; Wu et al, 2019). This could potentially suggest that the rate at which tannic acid associates with αSYN is much faster than its interaction with other signaling molecules involved in the pathway (Shaham-Niv et al, 2018).…”
Section: Discussioncontrasting
confidence: 98%
“…In addition to antioxidant effects, TA molecules also exhibit anti-inflammatory properties [ 41 ]. We examined the in vitro anti-inflammatory effects of TA-CaCO 3 by analyzing the mRNA expression of pro-inflammatory factors, such as cyclooxygenase-2 (COX-2), interleukin (IL)-1β, IL-6, matrix metalloproteinase (MMP)-3, MMP-13, and tumor necrosis factor (TNF)-α in lipopolysaccharide (LPS)-stimulated chondrocytes, because LPS treatment leads to the overexpression of these pro-inflammatory factors [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…58) Similarly, catechin, gallic acid, rutin and quercetin also reduce inflammatory marker in this model. [58][59][60] Moreover, kaempferol also inhibits hepatocyte apoptosis in d-GalN/LPS-induced acute liver failure mice 61) while tannic acid reduces NF-κB expression in LPS-induced BV2 microglial cells. 62) Furthermore, polyphenol extract also showed anti-inflamatory effect by reducing plasma LPS and IL-6 levels in human volunteers.…”
Section: Discussionmentioning
confidence: 97%